2018
DOI: 10.1002/jcb.27863
|View full text |Cite|
|
Sign up to set email alerts
|

The oncolytic virus H101 combined with GNAQ siRNA‐mediated knockdown reduces uveal melanoma cell viability

Abstract: Background Uveal melanoma (UM) is a severe human malignancy with a high mortality rate, as well as high metastasis and recurrence potential. The active mutation of G protein subunit alpha q (GNAQ) or G protein subunit alpha 11 (GNA11) is a major trigger for UM. Oncolytic adenovirus H101 (H101) is the first oncolytic virus approved for clinical applications in cancer therapy by the China Food and Drug Administration. We investigated whether combining H101 with the downregulation of GNAQ expression would act syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…GNAQ mutations are known to be associated with uveal melanoma (Jager et al, 2020). Combined therapy using si-GNAQ and H101 inhibits the proliferation of uveal melanoma cells by blocking the phosphorylation of mek1/2 and promoting the phosphorylation of yap (Li et al, 2019). Immune checkpoint blockade (ICB) aims to resolve tumor escape by reversing tumor immunosuppressive signals.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…GNAQ mutations are known to be associated with uveal melanoma (Jager et al, 2020). Combined therapy using si-GNAQ and H101 inhibits the proliferation of uveal melanoma cells by blocking the phosphorylation of mek1/2 and promoting the phosphorylation of yap (Li et al, 2019). Immune checkpoint blockade (ICB) aims to resolve tumor escape by reversing tumor immunosuppressive signals.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…The design of simplified analogues of FR900359 capable of effective GαQ/11 inhibition, including the small molecule YM-19, opens new perspectives for pharmaceutical development [ 247 ]. Among gene regulatory approaches, a combination therapy of oncolytic adenovirus H101 and siRNA mediating GNAQ downregulation was shown to induce UM cells apoptosis in in vivo activating UM cell apoptosis [ 248 ]. Moreover, a system for conjugating siRNAs to functionalized gold nanoparticles (AuNPs) able to recognize transcripts of mutant GNAQ mRNA was developed.…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 99%
“…The downregulation of GNAQ mutant expression using specific short interfering RNA (siRNA) decreased GαQ protein levels in UM cell lines, resulting in a decrease in Extracellular signal–Regulated Kinases (ERK) and AKT Serine/Threonine Kinase (AKT) signaling and in 5’ Adenosine Monophosphate-activated Protein Kinase (AMPK)-dependent autophagic cell death [29]. Other studies showed that the delivery of siRNA targeting mutated GNAQ through oncolytic viruses [30] or functionalized gold nanoparticles [31] inhibits UM cell viability and growth and may be useful for future gene regulatory therapeutic approaches.…”
Section: Targeting Driver Mutationsmentioning
confidence: 99%